Propuesta de mejoramiento en la cadena de producción y comercialización de balanceado en la asociación Produbal, del cantón Gonzanamá, provincia de Loja - Herrera Quito, Manuel Agustín (2017)
Advances in science and technology make companies today more competitive and globalized globally, this means that they are prepared to face new administrative challenges that requires that activities, functions and processes be improved so that Improve the entire organization in order to position itself in the market and be efficient in meeting the needs, tastes and preferences of its customers. The present thesis project is entitled: "PROPOSAL FOR IMPROVEMENT IN THE CHAIN OF PRODUCTION AND CHAIN OF MARKETING OF BALANCED IN THE ASSOCIATION PRODUBAL, CANTÓN GONZANAMÁ, PROVINCE OF LOJA". The general objective of this study is to Elaborate the Proposal for Improvement in the Production and Marketing Chain of Balanced Products in the Produbal Association of Gonzanamá, Loja Province. Methods such as deductive, inductive, analytical, statistical, were used for this purpose; The techniques of the survey applied to clients and employees, interviewing the manager of the company; As well as the procedures used for observation. The methodology helped to determine that the average times of the operating processes are currently: purchases 300 minutes, storage 315 minutes, planning 75 minutes, heavy without milling 210 minutes, heavy to mill 165 minutes, transportation 75 minutes, milling 150 minutes, Harvesting 105 minutes, mixed 150 minutes, diet 15 minutes, balanced weighing ready 90 minutes, bag sewing 60 minutes, storage in warehouse 90, distribution 135 minutes, all 1995 minutes. With the reengineering, a series of steps were avoided and the times were reduced: 245 minutes of storage, 270 minutes of storage, planning 65 minutes, heavy without grinding 190 minutes, heavy to grind 160 minutes, transport 60 minutes, grinding 110 minutes, harvesting 85 minutes, mixed 125 minutes, diet 10 minutes, balanced weighing ready 80 minutes, bag sewing 50 minutes, storage in warehouse 90, distribution 120 minutes, all 1660 minutes. For the application of new processes and reduction of the times a budget is required that will contribute to the improvement of the same for a value of $ 5,600.00. The main conclusion derives from the development of the present work of thesis, are synthesized as follows: The changes made in the processes of the PRODUBAL Association serve to benefit the company, and make the change radical, at the same time that the people who are in the process do not reject it, or that there is a contingency plan that helps To be for the benefit of the company